ZNF652-Induced circRHOT1 Promotes SMAD5 Expression to Modulate Tumorigenic Properties and Nature Killer Cell-Mediated Toxicity in Bladder Cancer via Targeting miR-3666 - Hu Ke; Jiabin Zhang; Fei Wang; Yunhe Xiong (Journal of Immunology Research)
Bladder cancer (BC) is the 9th most frequent diagnosed tumor and the 2nd most common urology tumor worldwide. Despite the considerable advancement that BC treatment has made recently, the five-year survival rate of BC remains unsatisfactory. Novel therapeutic strategies for BC clinical intervention are therefore urgently needed now more than ever. circRHOT1 is a newly identified circRNA that plays a crucial role in multiple types of tumorigeneses. However, it remains unclear whether circRHOT1 plays a functional role in BC progression. Our findings suggest that circRHOT1 was highly expressed in BC tumor tissues and cell lines. The results from CCK-8, EDU, Transwell migration, and NK cell-mediated cytotoxicity detection assays suggested that circRHOT1 knockdown could markedly suppress BC cell proliferation and migration level and could aggravate the sensitivity of BC cells to NK cells. Subsequently, we conducted bioinformatics analysis followed by RNA pull-down, ChIP, and luciferase reporter assays, from which we found that circRHOT1 expression in BC cells could be regulated by ZNF652, and circRHOT1 could promote SMAD5 expression to regulate BC cell cellular progression by sponging miR-3666. These results may provide a new direction for developing novel diagnostic or therapeutic targets for BC.